Perancangan Aplikasi Otomatisasi Pengontrolan Kamar Serta Proses Registrasi Tamu Di Nikita Hotel Bukittinggi - Mellya Rindhani Aditia; Afni Nia Sari (Journal Of Informatics And Busisnes, 2024)
Computer represent a created machine or appliance in the case af speed, correctness and process big information in member. Uppermost computer role progressively almost every big company. Even small company have gone to toward computerization. After done by research in Nikita Hotel Bukittnggi can know that there is internal issue do guest data processing, so that require sufficient time to yield a information. Therefore is to be designed by new system utilize to improve efektifitas and effeciency work at Nikita Hotel Bukittinggi. In marking of this report is done by some methode to process needed data, that is : first, field research to research object that is Nikita Hotel Bukittinggi. Second, library research whit book and literature related to problem of faced in making of this report. And the last, laboratoty research to test the truth of program weares and tested.